The Pilgrimage of Grace and the politics of the 1530s - Hoyle, R. W. (Richard W.) (Oxford University Press, 2001)
This is the first full account of the Pilgrimage of Grace since 1915. In the autumn and winter of 1536, Henry VIII faced risings first in Lincolnshire, then throughout Northern England.